Analisa Hubungan Stres Dan Pencetus Peningkatan Asam Lambung - Suminah Suminah; Leony Ciputri (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2023)
Bacground: Human life will always face with problems, the problems that come can cause the stres. Excessive stress will increase stomach acid production, which causes disturbances in the digestive tract. Indigestion appears in addition to an unbalanced lifestyle, it can also be caused by excessive stress. Methods: The research method used is by using literature review from text books and scientific publications. Results: Stress causes the stomach to become more sensitive, causing discomfort in the stomach. Chemical processes in the brain also change under conditions of stress, so that the enteric nervous system at the nerve endings in the stomach is more sensitive in reponding to pain and reduces levels of prostaglandins, which under normal conditions protect the stomach from the effects of stomach acid. Conclusion: Stress is a natural reaction of the body, which if excessive will cause a reaction to increase stomach acid.